(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The purpose of this study is to determine the amount of taxes collected on wheat imports from Peru and to identify the main supplier countries of Peru in terms of quantity and value. The method used is that of documentary review, extracting from the 7383 Customs Declarations of goods housed in the records of SUNAT Customs during the period from 2012 to 2021, the study took the values from the national subheading 1001.99.10.00 whose description is indicated as the other wheat, being the purely quantitative research with non-experimental and descriptive scope.